STRATEGI KOMUNIKASI BIDAN DALAM MENINGKATKAN PERILAKU HIDUP SEHAT IBU HAMIL DI KELURAHAN BULURI KECAMATAN ULUJADI - Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2020)
This research if to identify the Midwife’s Communication Strategy in Improving Healthy Life of Pregnant Mothers at Buluri, Ulujadi District. The base of this research is to analyze as many data sources as possible using descriptive method. This research is for investigating the activity and human labour. From this research results will be used to give recommendations for future uses. The subjects of this research are pregnant mothers in assumption that know and understand to be giving accurate informations. Data gathering method for this research are using interview and direct observation in the POSYANDU activities. This research proves that pregnant mothers don’t have understanding about healthy diet that pregnant mothers are needed. Other than that, they haven’t yet understand about healthy life and didn’t apply daily healthy life diet.